Building Teachers’ Data-use Capacity: Insights from Strong and Developing Coaches - Huguet, Alice; Marsh, Julie A; Farrell, Caitlin (Education Policy Analysis Archives, 2014)
Coaching has become a central strategy in district and school efforts to build teacher capacity to interpret and respond to student learning data. Despite their popularity, there is limited research on the implementation of these initiatives. This article begins to addresses this gap by examining the elements of a coach’s practice that appear to build teachers’ skills and knowledge to use data to guide instructional decisions. Drawing on sociocultural learning theory and interview and survey data collected in four middle schools—two with “strong” coaches and two with “developing” coaches—we find that coaching to build data-use capacity appears to rely less on the official title or model (i.e., data coach vs. instructional coach) and more on the diversity of coach practices as well as content area and interpersonal expertise. Further, administrators play an important role in shaping the work of a coach through their mediation of political dynamics in a school. The article concludes with implications for coaching practice, as well as suggestions to guide future research and theory development.